Análise de focos de γ-H2AX, PCNA e CASPASE-3 em mucosa gengival de indivíduos submetidos ao exame radiográfico panorâmico digital - Melo Netto, Francisco Marques de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Studies have shown concern with the progressive increase in the number of people who are exposed to ionizing radiation not natural (IR) and because of their association with cancer risk. The IR, depending on the quantity and dose intensity, is capable of causing genetic mutations and irreversible cell damage and, continuous exposure to ionizing radiation can cause damage to the deoxyribonucleic acid (DNA) molecule. In dental offices, in their different specialties patients are exposed to various doses of radiation X to obtain panoramic radiograph, periapical, occlusal and / or interproximal. This study examined specimens of the gingival mucosa collected from 12 subjects young adults exposed to X-rays to obtain panoramic radiograph, in periods of 2 hours, 5 hours and about 30 days after exposure. Histological slides were prepared for microscopic morphological analysis of specimens stained with hematoxylin and eosin (HE), and immunostained for the analysis of γ-H2AX histone proteins, Caspase 3 and PCNA involved in identifying DNA double strand break, apoptosis and cell proliferation, respectively. Comparative analysis of the values of the frequency γ-H2AX positive keratinocytes, Caspase-3-positive and PCNA positive in gingival epithelium between the experimental groups not showed statistically significant differences (> 0,05). The expression of proteins Histone γ-H2AX, PCNA and caspase 3 at the gingival epithelium did not differ in the two-hour period, five hours and 30 days of exposure to X-radiation in X-ray devices with radioactive average dose between 0.084 and 0.086 Gray

Estudos demonstraram preocupação com o aumento progressivo do número de pessoas que são expostas a radiação ionizante não natural (RI) e devido a associação destes com o risco de câncer. A RI, dependendo da quantidade e intensidade da dose, é capaz de causar mutações genéticas e danos irreversíveis às células, e a exposição continua a radiação ionizante pode causar lesões na molécula de ácido desoxirribonucleico (ADN). Nos consultórios odontológicos, nas suas diferentes especialidades os pacientes são expostos à várias doses de radiação X, seja para obtenção de radiografia panorâmica, periapical, oclusal e/ou interproximal. O presente trabalho analisou espécimes da mucosa gengival coletados de 12 indivíduos adultos jovens, expostos à radiação X para obtenção de radiografia panorâmica, nos períodos de 2 horas, 5 horas e cerca de 30 dias após à exposição. Lâminas histológicas foram confeccionadas para análise morfológica microscópica dos espécimes, corados em hematoxilina e eosina (H.E.), e imunomarcadas para a análise das proteínas histona γ-H2AX, Caspase 3 e PCNA, envolvidas na identificação de quebra da fita do DNA, apoptose e na proliferação celular, respectivamente. Análises comparativas dos valores da frequência de queratinócitos γ-H2AX-positivo, de Caspase 3-positivo e de PCNA-positivo, no epitélio gengival, entre os grupos experimentais não mostraram diferenças estatisticamente significantes ( > 0,05). A expressão das proteínas Histona γ-H2AX, Caspase 3 e PCNA, no epitélio gengival não diferiram no período de duas horas, cinco horas e 30 dias de exposição à radiação X em aparelhos radiográficos com dose radioativa média entre 0,084 e 0,086 Gray
Keywords: Radiação ionizante; Imunohistoquímica; Raios X; Caspase 3; Gengiva; Radiografia panorâmica; Radiation, Ionizing